Contribution of ICT to the Vietnamese Economy: An Input - Output Analysis - Dang, Thi Viet Duc (H. : ĐHQGHN, 2019)
This article uses Input-output (IO) analysis to evaluate the impact of ICT on the Vietnamese economy. Two IO tables are used, including tables from 2007 and 2012. The results show that ICT sectors were small in the Vietnamese economy and the spending on ICT products and services of an average sector of the economy was generally low. Regarding the impact on the output of other sectors, the research results reveal that ICT services and ICT media and content had an increasingly stronger link in production with other economic sectors of the economy. In contrast, the dispersion effect of the ICT manufacturing sector fell; despite this fact, ICT manufacturing retained a strong impact on the economy. In general, the impact of ICT was not much higher than other non-ICT sectors in Vietnamese economy. Results also reveal that the ICT sectors' backward linkages were stronger than forward linkages, i.e. the ICT sectors generated more impact on sectors which provided it input rather than on sectors that used its products and services. The study implies that if Vietnam seeks to enhance the economy, the government needs to implement specific policies that facilitate ICT industry and ICT usage.